Outro(s) lugar(es) de enunciação: a emergência do dialogismo em ambientes hipermidiáticos - Ribeiro, Maria Angélica Souza (2009)
Hipertextual logic, oriented by non-linear associative reasoning, favors a certain kind of navigational cartography; one that is less concerned with maps and representations than with random detours and states of wandering. Western thought, however, has placed order as the agnus dei of the 19th century, going from Descartes (and the birth of modern philosophy) to binarism and the speculative activity of scientific spirit. Dialogism allows a glimpse at the relation between terms, at first sight antagonistic, which reveals vectors of complementarity. The notions of dialogical openness and complexity of binarities (Peirce´s concept of brute force), when applied to hypermedia environments (territories of experimental language), enable a phenomenological approach to the research object at hand. It benefits, furthermore, the academic field of communication a research object in itself. This implies, succinctly, relating what is non-relational about scientific discovery (artistic sign applied to epistemic capacities) to external structures (of systemic origin, or media surroundings as hybrid language: images, sounds, videos, written text), making visible its sutures and endings